ANALISIS DETERMINAN EARNINGS MANAGEMENT - Dwi Nugraha Widhiwaluya; Faisal Faisal (Diponegoro Journal of Accounting, 2016)
This study aims to examines the relationship between the level of leverage, free cash flow, financing requirements, auditor’s independence and audit committee independence as a determinant of earnings management behavior. This study uses discretionary accruals as a proxy on earnings management.This study uses data manufacturing companies listed in Indonesia Stock Exchange (IDX) with a selected sample by purposive sampling method with a total sample of 43 companies and data used are annual report from 2012 period until 2014. To test the effect of each independent variable on the dependent variable using multiple linear regression. The results showed that the level of leverage negatively affect earnings management behavior while financing needs positively effect on earnings management behavior.